Identification and classification of project managers' knowledge needs - Mustapa, Muzani; Mustapa, Fara Diva; Ismail, Fuziah; Husin, Khairul Anuar
This paper is set-out to identify and classify knowledge and skills areas that construction project manager had to acquire in order to deliver the project successfully. Classifications of their knowledge are drawn apart from the correlation between determination of project success and project management besides established from project management ‘Body of Knowledge’. Range of project managers were interviewed in order to determine their knowledge needs and assessed on its impact and value to the project.